Quantification of MCT1 and CD147 in Red Blood Cells of Arabian and Quarter Horses - Regatieri, Inaê Cristina [UNESP]; Almeida, Maria Luiza Mendes [UNESP]; Teixeira Neto, Antônio Raphael; Curi, Rogério Abdallah [UNESP]; Ferraz, Guilherme Camargo [UNESP]; Queiroz-Neto, Antonio [UNESP] (Elsevier, 2016)
During anaerobic glycolysis for energy production, lactate and H+ ions accumulate in muscle fibers and pass into the blood stream. The monocarboxylate transporter isoform 1 (MCT1) and its ancillary protein cluster of differentiation 147 (CD147) transport H+ and lactate ions from the plasma into red blood cells (RBCs), thereby maintaining acid/base homeostasis and retarding systemic acidosis and fatigue. The aim of this study was to compare the levels of MCT1 and CD147 protein in the RBC membranes of Arabian and Quarter Horses with different levels of athletic ability. Blood samples were collected from 40 Arabian and 40 Quarter Horses, both males and females, ranging from 3 to 16 years and 2 to 23 years, respectively. The horses were divided into two groups: 20 animals of low performance and 20 animals of high performance for each breed. The amount of MCT1 and CD147 in the plasma membranes of their RBCs was determined by Western blotting analysis with arbitrary optical density (OD) units, using a human-specific anti-MCT1 and anti-CD147 antibodies that were previously validated for horses. The means ± standard errors were analyzed by repeated measures analysis of variance using the PROC MIXED procedure of SAS software. The effect of age was included as covariate and sex as a class effect in the model. The correlations were analyzed by Pearson correlation test at P < .05. Monocarboxylate transporter isoform 1 with a molecular mass of approximately 52 and 49 kDa was found in the RBC membranes of all the Arabian and Quarter Horses, respectively. Cluster of differentiation 147 also was observed in all Arabian and Quarter Horses at approximately 52 and 48 kDa, respectively. A positive correlation was observed between the total amount of MCT1 and CD147 (r = 0.932, P < .001) in the RBC. The amount of MCT1 was significantly (P < .0001) higher in Quarter Horses (3.03 ± 0.37 OD) than in Arabians (1.02 ± 0.07 OD). Quarter Horses (3.23 ± 0.39 OD) also showed increased contents of CD147 than Arabians (0.89 ± 0.06 OD). However, there was no statistical difference in the amount of the protein between the low- and high-performance groups in either breed. Results indicate that the levels of MCT1 and CD147 are different between Arabian and Quarter Horses and the most probable explanation is that different pathways are used for the production of energy for each breed.
Keywords: Anaerobic metabolism; Fatigue; Lactate; Performance; Western blotting